2017
DOI: 10.18632/oncotarget.20102
|View full text |Cite
|
Sign up to set email alerts
|

Cancer testis antigen Sperm Protein 17 as a new target for triple negative breast cancer immunotherapy

Abstract: Breast carcinoma is a major health issue for millions of women. Current therapies have serious side effects, and are only partially effective in patients with metastatic tumors. Thus, the need for novel and less toxic therapies is urgent. Moreover, hormonal and antibody therapies effective in other subtypes are not effective in Triple Negative Breast Cancer (TNBC). Immunotherapeutic strategies directed against specific tumor-associated antigens (TAAs) and mediated by specific cytotoxic T lymphocytes (CTL) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The possible connection between gametogenesis and cancer development has been previously suggested; for example, the expression of the synaptonemal complex protein 1 (SCP1), a protein selectively expressed during the meiotic prophase of the spermatocyte, has been reported in several tumour types, including: glioma, breast cancer, and melanoma, suggesting that it may contribute to genomic instability [ 59 ]. The sperm protein 17 (Sp17), which was primarily thought to be restricted only to developing spermatozoa and mature spermatids, has been shown to be expressed in breast cancer, multiple myeloma, epithelial ovarian cancer, and esophageal cancer, making it a potential candidate target for immunotherapy [ 60 , 61 ]. The MNS1 gene was shown to be down-regulated in an oxaliplatin-resistant human colon cancer cell line, and up-regulated in an oxaliplatin-sensitive human colon cancer cell line after continuous treatment with oxaliplatin for 24 h, suggesting its molecular role in chemoresistance [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible connection between gametogenesis and cancer development has been previously suggested; for example, the expression of the synaptonemal complex protein 1 (SCP1), a protein selectively expressed during the meiotic prophase of the spermatocyte, has been reported in several tumour types, including: glioma, breast cancer, and melanoma, suggesting that it may contribute to genomic instability [ 59 ]. The sperm protein 17 (Sp17), which was primarily thought to be restricted only to developing spermatozoa and mature spermatids, has been shown to be expressed in breast cancer, multiple myeloma, epithelial ovarian cancer, and esophageal cancer, making it a potential candidate target for immunotherapy [ 60 , 61 ]. The MNS1 gene was shown to be down-regulated in an oxaliplatin-resistant human colon cancer cell line, and up-regulated in an oxaliplatin-sensitive human colon cancer cell line after continuous treatment with oxaliplatin for 24 h, suggesting its molecular role in chemoresistance [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…CTAs are involved in cellular proliferation, migration/motility, colonization, and cell division in normal germ cells, while in cancer cells, CTAs have been implicated in sustenance of growth, maintaining nutrient and oxygen supply through the activation of angiogenesis, evading apoptotic cell death, increase in tissue invasiveness and metastasis, and development of resistance to anti-cancer drugs [214]. In breast cancer, CTAs, such as MAGE-1, AKAP4, NY-BR-1, CTAG1, BAGE1, MAGE-A10, SP17, NY-ESO-1, and MAGE-A, were found to play important roles in activating cell proliferation, inhibition of apoptosis, and promoting tissue invasion and metastasis [5,[215][216][217][218][219][220][221][222]. The CTA, AKAP4, in particular seems to be an interesting candidate for a serum-based diagnostic test for the early detection and diagnosis of breast cancer [221].…”
Section: Metformin and Breast Cancer Biomarkersmentioning
confidence: 99%
“…The CTA, AKAP4, in particular seems to be an interesting candidate for a serum-based diagnostic test for the early detection and diagnosis of breast cancer [221]. SP17, MAGE-A, NY-ESO-1, and MAGE-A10 on the other hand were more specifically associated with TNBCs [216,218,219]. There is but little evidence that could link the occurrence of diabetes to the expression of the CTAs, which can then be possibly used as diagnostic markers to link diabetes and the incidence of breast cancer or even a specific kind of breast cancer.…”
Section: Metformin and Breast Cancer Biomarkersmentioning
confidence: 99%
“…Taylor et al has reported that, a vaccine directed against three CTAs-CTAG1, BAGE1 and MAGE-A10, can target two-thirds of breast cancers and can specifically target cytotoxic-T-lymphocyte responses [211]. Within the more stubborn TNBCs, when compared to other forms of breast cancer, CTA -SP17 is expressed in TNBCs [212]. NY-ESO-1 is expressed in a significant subset of TNBC subjects, leading to high humoral immune responses and therefore TNBC patients should benefit from targeted therapies against NY-ESO-1 [213].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…The frequent occurrence of specific CTAs in breast cancers indicate a possibility to define and include new targets for therapeutic intervention [210,211]. Certain CTAs were expressed in the more stubborn TNBCs [212][213][214][215]. However, there is little evidence that links diabetes and breast cancer in terms of the expression and importance of CTAs in breast cancer.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%